Eyewear for Rugby Union: Wearer characteristics and experience with rugby goggles - Little, J.-A.; Eckert, F.; Douglas, M.; Barrett, B. T. (International Journal of Sports Medicine, 2020)
Unlike many other sports, Rugby Union has not permitted players to wear spectacles or eye protection. With an industrial partner, World Rugby developed goggles suitable for use while playing rugby for the purposes of growing participation amongst those that need to wear corrective lenses. This study reports on the profile and experiences of goggle wearers. 387 players received the goggles. Data were obtained from 188 (49%) using an online, 75-item questionnaire. 87% "strongly agreed/agreed" that goggles are beneficial and 75% are happy with goggle performance. Common problems reported by 49.7 and 32.6% of respondents were issues with fogging-up and getting dirty. 15 (8%) players stopped wearing the goggles because of fogging-up, limits to peripheral vision and poor comfort/fit. Injuries were reported in 3% of respondents. In none of these cases did the player stop wearing the goggles. From the positive experience of players in the trial, the goggles were adopted into the Laws of the game on July 1, 2019. As the need to correct vision with spectacles is common, and contact lenses are not worn by 80%+of spectacle wearers, the new Rugby goggles will widen participation for those that need to wear refractive correction, or have an existing/increased risk of uniocular visual impairment.